2016
DOI: 10.1039/c5nr08836d
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, flexible and mechanically robust perovskite solar cells on inverted nanocone plastic substrates

Abstract: Utilization of nanostructures on photovoltaic devices can significantly improve the device energy conversion efficiency by enhancing the device light harvesting capability as well as carrier collection efficiency. However, improvements in device mechanical robustness and reliability, particularly for flexible devices, have rarely been reported with in-depth understanding. In this work, we fabricated efficient, flexible and mechanically robust organometallic perovskite solar cells on plastic substrates with inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 44 publications
1
63
0
1
Order By: Relevance
“…Compared with the planar structure, it has been demonstrated that devices in meso‐structure show better controlling of the perovskite crystallization process and smaller hysteresis of the as‐prepared device . Interestingly, Tavakoli et al proved that the nanostructured substrate can assist in relaxing stress and strain upon bending, as they achieved mechanically robust PSCs on plastic substrates with an inverted nanocone structure . The efficiency of PSCs based on ZnO meso‐strcuture has been improving in the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the planar structure, it has been demonstrated that devices in meso‐structure show better controlling of the perovskite crystallization process and smaller hysteresis of the as‐prepared device . Interestingly, Tavakoli et al proved that the nanostructured substrate can assist in relaxing stress and strain upon bending, as they achieved mechanically robust PSCs on plastic substrates with an inverted nanocone structure . The efficiency of PSCs based on ZnO meso‐strcuture has been improving in the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…To this day, most nanowires, nanotubes and nanoparticles have been produced successfully using AAO templates 15 . Furthermore, flexible and mechanically robust PSCs have been fabricated on plastic substrates with inverted nanocone AAO structures 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from causing inconspicuous interference to QCMs’ readings and eventually film quality, especially when precursors of similar physical properties are being evaporated simultaneously, it significantly increases the fabrication complexity and production cost. To solve this problem, sequential vapor deposition comes in and is capable of acquiring high‐quality and uniform perovskite films for high‐performance devices . In reality, sequential deposition can be readily implemented in a large scale using an in‐line process flow.…”
Section: Resultsmentioning
confidence: 99%